Total Quality Management Pengaruhnya Terhadap Kinerja Keuangan Rumah Sakit di RSU ‘Aisyiyah Ponorogo - Eva Nurdiyanti; Riduwan; Salamatun Asakdiyah (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to examine the impact of Total Quality Management (TQM) implementation on the financial performance of RSU 'Aisyiyah Ponorogo, focusing on seven key dimensions: managerial leadership, data-driven decision-making, process management, continuous improvement, employee involvement, supplier relationships, and customer focus. TQM is regarded as a strategic approach to enhance organizational effectiveness and efficiency by engaging all institutional elements in continuous improvement efforts. The research employs a quantitative approach using a survey method. Data were collected through a closed-ended questionnaire based on a Likert scale, distributed to 105 respondents—employees of RSU 'Aisyiyah Ponorogo who have worked for a minimum of three years and have been involved in TQM implementation. Data analysis was conducted using validity and reliability tests, as well as multiple linear regression analysis with SPSS version 25. The results indicate that, individually, all independent variables have a positive and significant effect on financial performance. Simultaneously, the implementation of TQM significantly contributes to enhancing operational efficiency, reducing waste, and strengthening the hospital’s competitiveness by improving customer satisfaction and fostering effective collaboration with suppliers. The roles of managerial leadership and data-driven decision-making are found to be crucial in steering cost-efficiency and strategic optimization. Moreover, active employee engagement and continuous improvement initiatives directly support the financial stability and growth of the hospital. This study concludes that integrated TQM implementation not only improves service quality but also strengthens the hospital’s financial performance in a sustainable manner. The findings provide theoretical contributions to the development of quality management in the healthcare sector and practical implications for hospital policymakers in designing strategies to enhance financial performance.